Cochlear implantation performance outcomes in patients over 80 years old. Issue 3 (27th May 2022) - Wichova, Helena; Mills, Dawna; Beatty, Sarah; Peng, Kevin; Miller, Mia
Abstract: Objective: To examine device datalogging characteristics and postoperative performance in the very elderly CI users. Methods: Retrospective chart review of postoperative speech recognition outcomes and datalogging characteristics in patients older than 80 years old who underwent cochlear implantation and remain active users with longer than 6 months post‐activation follow‐up. Results(s): The mean age at implantation was 84.8 ± 3.8 years old. Pre‐ and post‐operative AzBio sentences in quiet scores were 12.4 ± 16.4% and 53.0 ± 23.5%, respectively ( p < .001). Pre‐ and post‐operative consonant‐nucleus‐consonant (CNC) word scores were 9.4 ± 12.8% and 40.5 ± 20.7%, respectively ( p < .001). A nonsignificant negative correlation was noted between the age of implantation and postoperative CNC words and AzBio sentence performance. Significantly decreased performance was noted in the subpopulation with a preoperative diagnosis of dementia. Mean daily use was 10.9 h per day. When available the mean daily usage distribution was 16% speech in noise, 19.1% speech, 51% quiet, 3.8% music, and 9.6% noise. A significant positive correlation was noted between daily use and AzBio sentence and CNC word performance. Conclusions: Very elderly patients have significant postoperative auditory performance benefits after CI. Mean daily use is comparable to previously published results in the younger population. Age of implantation does not play a significant role in overall performance. Elderly patients who are medically cleared for implantation receive significant postoperative benefits. Abstract : Cochlear implantation in the very elderly (older than 80 years old) is becoming more common and outcomes data for this subgroup is still lacking. Our study found that, very elderly patients have significant postoperative auditory performance benefits after CI with mean daily use comparable to previously published results in the younger population.